Covid-19 and the Growth of Telemedicine in Nigeria: Prospect, Legal Issues and Challenges - Ikubanni, Oluwaseye Oluwayomi; Adeboye, Oluwaseye Thompson; Afolabi, Egbewole Qasim; Adams, Omowonuola; Awoniyi, Adeola Roseline (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
Though telemedicine is not a recent development, the advancement of technology and the advent of COVID-19 especially its social distancing and lockdown policies triggered its wide acceptance as a means of accessing healthcare services in Nigeria. This paper, therefore, examines the operation of telemedicine in Nigeria by navigating through its legal framework and challenges. The study underscores the loopholes in the existing laws on telemedicine in Nigeria. The study adopts both quantitative and qualitative research methodologies. The quantitative methodology involves the use of an online questionnaire survey sent to 131 respondents (randomly selected) who reside in Nigeria. Analytical and descriptive methods were utilised in analysing the data obtained. The qualitative methodology involves the reliance on primary and secondary sources material. The study finds that lack of a specific legal framework, poor power supply, illiteracy, lack/poor internet services, cyber fraud, and so on are the factors that have stifled the growth of telemedicine in Nigeria. The study concludes that though telemedicine has come to stay in Nigeria, the country may not enjoy all the blessings that telemedicine offers other great nations with more developed economies if these challenges are not addressed swiftly. The study therefore recommends amongst others the enactment of a law that specifically regulates telemedicine in Nigeria, especially in the area of teleconsent, data protection, and privacy This will enhance the exponential growth of telemedicine in Nigeria.